EP 59. Gait specific modulation of local field potentials in the STN of patients with Parkinson's disease. Issue 9 (September 2016) - Hell, F.; Mehrkens, J.H.; Plate, A.; Bötzel, K.
Abstract : PD patients with implanted DBS electrodes allow for the investigation of basal ganglia activity during gait. Whereas the overall spectral content of local field potentials (LFP) in the BG is known to change with movement, it is still unclear how exactly the BG-LFP change during gait. We investigated the electric local field potentials of the STN of 10 patients with PD during gait. Gait parameters were recorded with inertial sensor units and the gait was subsequently analyzed in parallel to the electrophysiological activity in Matlab. Additionally, we recorded LFPs during rest and control experiments to probe for movement related artifacts. Stimulation was off in all experiments reported here. On a group level, a frequency analysis shows that the high beta frequency band gets significantly downregulated during gait as compared to sitting rest. On an individual level, a linear classifier trained with frequency profiles of small epochs of LFP activity recorded during gait and rest can distinguish between walking and resting episodes with a mean classification accuracy across all patients of 90%. A time–frequency analysis on the group level reveals a distinct modulation pattern. Whereas low frequencies in the theta and alpha range and high frequencies in the gamma range are modulated up and down time-locked to the gait cycle, the beta band gets modulated down during the complete gait cycle.